PENERAPAN METODE BERCERITA DALAM MENGEMBANGKAN MORAL DAN AGAMA ANAK USIA DINI - Khairiyah, Dina (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2019)
The application of the story-telling method is one method that can develop several aspects of early childhood development, such as moral and religious development. By using the story-telling method a teacher can introduce the moral and religious foundations in early childhood. Our research approach uses library research as a place or source of reference. The aim of this research is to find out the method of developing religious morals in early childhood with the story method. Based on the results of the study, in general the method of storytelling to develop the moral and religious potential of students is to use the method of reading directly from story books, telling stories using picture illustrations from books, telling stories, telling stories using flannel boards, telling stories using puppet media, dramatization a story, and a story while playing fingers. The contents in the story must contain religious aspects, pedagogical aspects, and psychological aspects, which contain material stories about the stories of prophets, friends, scholars, and pious people